2012
DOI: 10.1089/met.2012.0045
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sleep Apnea and Insomnia on Blood Levels of Leptin, Insulin Resistance, IP-10, and Hydrogen Sulfide in Type 2 Diabetic Patients

Abstract: Introduction: Sleep deficits associated with sleep apnea and insomnia increase the risk of vascular inflammation and insulin resistance. This study examined the hypothesis that inflammation markers are higher in those diabetic patients who experience sleep deficits compared with those without any history of a sleep disorder. Methods: Fasting blood was obtained after written informed consent, and sleep disorder histories were obtained from type 2 diabetic patients (n = 81) attending clinics of the Louisiana Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
2
24
0
1
Order By: Relevance
“…Few studies, however, reported the relationships between IP10 and sleep disturbance. Jain et al found that IP10 levels were elevated in type 2 diabetes patients with insomnia, sleep apnea or both [35]. We found that IP10 in healthy menopausal women was significantly related to poor sleep quality as well as low sleep efficiency.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Few studies, however, reported the relationships between IP10 and sleep disturbance. Jain et al found that IP10 levels were elevated in type 2 diabetes patients with insomnia, sleep apnea or both [35]. We found that IP10 in healthy menopausal women was significantly related to poor sleep quality as well as low sleep efficiency.…”
Section: Discussionmentioning
confidence: 47%
“…IP10, IL6 and hs-CRP have been demonstrated to be risk factors for metabolic and cardiovascular diseases [35,46,47]. Epidemiological studies consistently demonstrate associations between suboptimal sleep and systemic chronic diseases such as coronary heart disease, stroke, and diabetes [43,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that diabetic patients and diabetic animals also have reduced blood levels of H 2 S [Brancaleone et al, ; Jain et al, ; Whiteman et al, ]. H 2 S is increasingly being recognized as an important signaling molecule and has been shown to modulate a variety of biological effects that may mediate the protection of various organ dysfunctions [Szabó, ; Whiteman et al, ; Jain et al, ; Manna and Jain, ]. Studies in the literature report the protection of pancreatic β‐cells from oxidative stress by H 2 S via an anti‐oxidative mechanism and the activation of AKT signaling [Kaneko et al, ; Taniguchi et al, ].…”
mentioning
confidence: 99%
“…Separately, although initial insomnia was not significantly associated with incident hypertension, middle insomnia was associated with a 20% increased risk and late insomnia was associated with a 14% increased risk. In addition to hypertension, several studies have shown insomnia to be associated with inflammation (Jain et al, 2012; Laugsand et al, 2012; Motivala, 2011; Okun et al, 2011), impaired heart rate variability (De Zambotti et al, 2011; Israel et al, 2012; Spiegelhalder et al, 2011; Stein & Pu, 2012), and other risk factors (Balbo et al, 2010; Lattova et al, 2011; Laugsand et al, 2013; Strand et al, 2013). …”
Section: Cardiometabolic Disease Risk Associated With Sleep Disturbancementioning
confidence: 99%